The Effectiveness of Kahoot Game-Based Learning and Social Support Coping Strategy among Undergraduate Students with Academic Problems - Kuncharin, Linatda (วารสารนวัตกรรมการศึกษาและการวิจัย, 2024)
The aim of this study was to explore the effectiveness of Kahoot game-based learning and social support coping strategy among undergraduate students with academic problems and to examine whether on how students expected about the effectiveness of using Kahoot game-based learning and social support coping strategy with academic problems among undergraduate students. In this study, the researcher applied sequential mixed method study to determine the effectiveness of the Kahoot game based-learning and social support coping strategy with academic problems among undergraduate students. A total of 379 undergraduate students participated in this study. The quantitative study was evaluated by using descriptive statistics such as mean, standard deviation, while, correlation, and regression were used to answer the research question 1 (hypothesis 1 and hypothesis 2). In addition, a qualitative study used thematic analysis to interpret the data. The regression analysis showed that Kahoot game and academic problems among undergraduate students had negative and significant relationship (R-square = 0.387; F = 22.844; Beta (β) = -0.417; T-value = -4.419; and P-value = 0.000). Meanwhile, the regression analysis found that social support coping strategy and academic problems among undergraduate students had negative and significant relationship (R-square = 0.096; F = 7.474; Beta (β) = -0.290; T-value = -2.643; and P-value = 0.000). Three students were interviews, students who agreed to participate in the study, they revealed that Kahoot game-based learning and social support coping strategy were effective among undergraduate students with academic problems. The results have significance practical implication for Thai government, university, lecturers, and undergraduate students.